Mengatasi Distorsi Kognisi pada Remaja - Camelia Kristika Pepe; Meilanny Budiarti Santoso (Social Welfare Study Program, 2016)
Teenager is one of the phase that will be experienced in by all of an adult human being. The failure in meet the needs and the development of duty during adolescence can become difficulties to have a self actualization. The difficulties’ symptoms can be started from the appearance of thought and selftalk negative on theirselves. It is known with the term cognitive distortion. The distortion is cognitive deviation the thought that is experienced by individuals. Deviation this thinking consist of personalization, over generalization, mental filter, mind reading, development with equity should the statement and also minimization. Social workers as a profession assistance having stage practices to do and starting from initial phase namely assessment into termination. In the case of clients by distortion cognitive, social workers may provide various technique therapy to change the mind automatic (selftalk) for client from negative to be positive selftalk. One technique therapy which could be provided by a social worker in clients by distortion cognitive is therapeutic cognitive three colom. This therapy is intended to transform the mind clients which was originally irrational being rational, reduce their negative thoughts and change dysfunctional thought process . When social workers use this therapy in help clients the clients should make self report which serves to see the replacement of irrational thought after they have been given the therapy.Keywords: Distorsi Kognitif, Selftalk, Kognitif Tiga Kolom.